LARRY J. HACKMAN, ed., Many Happy Returns: Advocacy and the Development of Archives - Hendry, Julia (Archivaria, 2012)
Many Happy Returns: Advocacy and the Development of Archives. LARRY J. HACKMAN, ed. Chicago: Society of American Archivists, 2011. xi, 411 p. ISBN 1-931666-37-7.